2007
DOI: 10.1162/jocn.2007.19.7.1175
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Iconic Gestures in Speech Disambiguation: ERP Evidence

Abstract: The present series of experiments explored the extent to which iconic gestures convey information not found in speech. Electroencephalogram (EEG) was recorded as participants watched videos of a person gesturing and speaking simultaneously. The experimental sentences contained an unbalanced homonym in the initial part of the sentence (e.g., She controlled the ball ...) and were disambiguated at a target word in the subsequent clause (which during the game ... vs. which during the dance ...). Coincident with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
214
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(236 citation statements)
references
References 40 publications
(55 reference statements)
21
214
1
Order By: Relevance
“…When the hand movements offered no helpful cue for the interpretation of the sentence (i.e., in the grooming condition), word meaning frequency had a significant (albeit small) influence on target word selection. These results are in line with our previous findings in showing that listeners use the information provided by iconic gestures to disambiguate speech (Holle and Gunter, 2007). In the absence of a cue for meaning selection, word meaning frequency influences which meaning of the ambiguous sentence is selected (Holle and Gunter, 2007, Exp. 3).…”
Section: Behavioral Datasupporting
confidence: 92%
See 3 more Smart Citations
“…When the hand movements offered no helpful cue for the interpretation of the sentence (i.e., in the grooming condition), word meaning frequency had a significant (albeit small) influence on target word selection. These results are in line with our previous findings in showing that listeners use the information provided by iconic gestures to disambiguate speech (Holle and Gunter, 2007). In the absence of a cue for meaning selection, word meaning frequency influences which meaning of the ambiguous sentence is selected (Holle and Gunter, 2007, Exp. 3).…”
Section: Behavioral Datasupporting
confidence: 92%
“…In light of the rather low amount of dominant target word selections after grooming videos (just above chance level), it is a possibility that word meaning frequency was not effectively varied in this study. Note, however, that in a number of previous experiments, the same set of homonyms elicited strong effects of word meaning frequency (Gunter et al, 2003;Holle and Gunter, 2007).…”
Section: Subordinate > Dominantmentioning
confidence: 77%
See 2 more Smart Citations
“…pictures, line drawings, or gestures) into a context have reported a more frontal scalp distribution for the N400 effects (e.g. Federmeier, and Kutas, 2001;Ganis, Kutas, and Sereno, 1996;Holle, and Gunter, 2007;Willems et al, 2007). Here, it is suggested that in Experiment 2 the additional attempt to predict upcoming words involves (parts of) the language production system (Pickering, and Garrod, 2007).…”
Section: Discussionmentioning
confidence: 82%